SELF-BLAME IN PARENTS OF CHILDREN WITH AUTISM SPECTRUM DISORDER AND CHILDREN WITH PHYSICAL DISABILITIES: THE ROLE OF A CHILD’S PROBLEM BEHAVIOR AND PERSONALITY TRAITS - Čolić, Marija; Milačić Vidojević, Ivona (Specijalna edukacija i rehabilitacija, 2020)
Little is known about self-blame in parents of children with disabilities despite previous findings of negative effect of self-blame on well-being. Thus, the aim of the present research was to explore self-blame among Serbian parents of children with autism spectrum disorder and physical disabilities. In addition, we wanted to examine the effect of children’s problem behavior, personality traits, perceived and experienced stigma, and sociodemographic characteristics on parental self-blame. The convenient sample included 82 parents from several large cities in the Republic of Serbia. For the purpose of this study, the seven-item Parental Self-Blame Scale was developed. Overall, parents reported a lower level of self-blame. A total of 22% had moderate to high degree of self-blame. Furthermore, self-blame did not differ between two groups of caregivers. Additionally, with an increase in children’s emotional problems and a decrease in agreeableness, parents blamed themselves more. No effects of sociodemographic variables nor effects of perceived and experienced stigma on self-blame were found. Our results suggest that in supporting families of children with autism spectrum disorder and physical disabilities, clinicians need to take into consideration the variability in their experiences and that the Parental Self-Blame Scale could be used to identify the most vulnerable individuals. Additionally, support should also be provided to the child and thus decrease the child’s emotional problems and consequently support the whole family.